Educational Financing Management: A Qualitative Multisite Study of SMA Negeri 13 Medan and SMA Negeri 1 Deli Tua, Deli Serdang Regency - Anna Simanjuntak; Amiruddin Siahaan; Abdurrahman Abdurrahman (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
The current findings are based on the importance of educational financial management in supporting quality improvement, operational efficiency, and equitable educational services. Although the government has allocated an education budget in accordance with the 1945 Constitution and the National Education System Law, the reality on the ground shows a disparity in funding between urban and suburban schools. SMA Negeri 13 Medan, as a more established school with greater access to funds, faces issues of transparency and accountability in the use of funds. Meanwhile, SMA Negeri 1 Deli Tua faces challenges of limited funds and the need for a more optimal management strategy in allocating budgets to meet learning and school operational needs. This study uses a qualitative approach with a multisite design, covering analysis of planning, implementation, organization, supervision of funding, as well as obstacles and efforts to resolve them. Interviews were conducted with school principals, teachers, and school committee members at each school. The results of the study reveal that the implementation of education financing at SMA Negeri 13 Medan and SMA Negeri 1 Deli Tua has been carried out in accordance with the principles of good financial management in education. Both schools demonstrated compliance with the technical guidelines for the School Operational Assistance and the School Financial Management Plan, regular reporting, and public transparency through the School Operational Assistance information board and accountability meetings. Both schools have successfully implemented the principles of good school financial management consistently, thereby having a direct impact on improving the quality of educational services. This study recommends policies to improve transparency, efficiency, and accountability in the management of education funds. In addition, the findings of this study contribute to strengthening the literature on education financing management, particularly at the public high school level, and support efforts to equalize the quality of education in Indonesia through strengthening school financial management.